Profile of Recombinant Pro-urokinase Given by Intraarterial versus Intravenous Routes of Administration in a Canine Thrombosis Model - Burke, Sandra E.; Lubbers, Nathan L.; Nelson, Richard A.; Wegner, Craig D.; Cox, Bryan F. (Thrombosis and Haemostasis, 1999)
Catheter-directed thrombolysis has gained increasing acceptance for the treatment of patients who present with vascular occlusion; however, intravenous injection may be preferable in selected patients. Recombinant prourokinase (r-proUK) is a recently-developed fibrin-selective thrombolytic agent with specificity for clot-bound plasminogen. To compare the effects of r-proUK on clot lysis and restoration of blood flow when injected by either intraarterial or intravenous routes of administration, we utilized a dog model of arterial thrombosis in which a radiolabelled clot is formed in the femoral artery. The r-proUK was given by intravenous infusion to one group of 18 animals in doses ranging from 10,000 IU/kg to 100,000 IU/kg; a second group of 27 dogs was treated with r-proUK administered by the intra-arterial route in a dose range from 300 IU to 10,000 IU. Clot lysis was measured by monitoring the loss of counts from the radiolabelled clot over time; blood flow was also monitored throughout the experimental period. Animals which received intravenous treatment showed dose-related clot lysis ranging from 14% to 70% at 2 h, while those which received intra-arterial infusions showed lysis ranging from 22% to 79% over the same period. For similar degrees of clot lysis attained at the highest dose levels of 100,000 IU/kg and 10,000 IU, blood flow was restored to 77% and 35% of control levels in dogs which received intravenous and intraarterial treatment, respectively. The hemostatic protein fibrinogen was not reduced in any of the treatment groups. The results indicate that 100 times more intravenous than intra-arterial r-proUK is required to produce similar clot lysis in this canine model, and that the agent can be administered at this level without induction of a systemic lytic state.